Development of a patient‐centred, patient‐reported outcome measure (PROM) for post‐stroke cognitive rehabilitation: qualitative interviews with stroke survivors to inform design and content. (5th December 2014) - Patchick, Emma L.; Horne, Maria; Woodward‐Nutt, Kate; Vail, Andy; Bowen, Audrey
Abstract: Background: Improving cognition is service users' top research priority for life after stroke, and future research should include outcomes that they deem important. Patient perspectives on outcomes are collected using patient‐reported outcome measures (PROMs). There is currently no patient‐centred PROM specific for cognitive rehabilitation trials. Objective: Inform PROM development by exploring stroke survivor perspectives on the important, measurable impacts of persisting post‐stroke cognitive problems. Design: Qualitative semi‐structured interviews in participants' homes. Participants: Purposive sample of 16 cognitively impaired stroke survivors at least six months post‐stroke. Methods: Interviews used a schedule and communication aids developed through patient consultation. Interviews were transcribed verbatim with non‐verbal communication recorded using field notes. Data were analysed using a framework approach to find commonalities to shape the focus and content of an outcome measure. Results: Participants identified important impacts of their 'invisible' cognitive problems, outside of other stroke‐related impairments. Cognitive problems exacerbated emotional issues and vice versa. Changes in self‐identity and social participation were prominent. Impact was not spoken about in terms of frequency but rather in terms of the negative affect associated with problems; terms like 'bothered' and 'frustration' were often used. Conclusions: The results support the development of a PROM specifically designed to address the impact of cognitive problems. It should: include items addressing a comprehensive range of cognitive skills; ask questions about mood, self‐identity and social participation; use accessible wording that respondents understand and endorse; measure impact rather than frequency; and explore perceived impact on carers.